2014
DOI: 10.3390/molecules190913122
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Broth in Tyrosinase- and Melanogenesis Inhibition

Abstract: Abstract:Fermented broth has a long history of applications in the food, pharmaceutical and cosmetic industries. Recently, the use of fermented broth in skin care products is in ascendance. This review investigates the efficacy of fermented broth in inhibiting tyrosinase and melanogenesis. Possible active ingredients and hypopigmentation mechanisms of fermented broth are discussed, and potential applications of fermented broth in the cosmetic industry are also addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 95 publications
1
51
0
Order By: Relevance
“…The mitogen‐activated protein kinase (MAPK) signalling pathway (including ERK, P38 and JNK) has been shown to play a key role in melanogenesis by affecting tyrosinase . It has been found that activation of the MAPK signalling pathway can upregulate the expression of TYR, TYRP1 and TYRP2 to promote melanogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…The mitogen‐activated protein kinase (MAPK) signalling pathway (including ERK, P38 and JNK) has been shown to play a key role in melanogenesis by affecting tyrosinase . It has been found that activation of the MAPK signalling pathway can upregulate the expression of TYR, TYRP1 and TYRP2 to promote melanogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…The MITF gene itself is a target of cAMP signaling induced by α-MSH, and predominantly regulates tyrosinase and TRP-1 protein expression [35,36,37]. In the cAMP-dependent signaling pathway, the dual phosphorylation of the cAMP response element binding protein (CREB), mediated by the kinase activities of ribosomal S6 kinase (RSK) and PKA, has been found to activate MITF transcription [38,39]. Furthermore, it has been reported that suppression of the cAMP-dependent signaling pathway causes MITF degradation in α-MSH-stimulated melanoma cells [40].…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation of Raf-1 activates (phosphorylates) a series of mitogen-activated protein kinases (MEKs), extracellular signal-regulated kinases (ERKs), RSKs, and CREB in the mitogen-activated protein kinase (MAPK) cascade [41]. In addition, the MAPK family proteins including ERK, p38, and c-Jun N-terminal kinase (JNK) are also known to play crucial roles in melanogenesis [39]. The phosphorylation of p38 induces MITF expression, whereas the phosphorylation of ERK and JNK downregulate melanin synthesis [39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing interest in the use of plant natural products for inhibition of melanogenesis [17,18]. However, little is known about the effect of proso millet on tyrosinase activity.…”
Section: Introductionmentioning
confidence: 99%